Broadcast Boom Sprayer Calibration - Thomas W. Dean; Frederick M. Fishel (EDIS)
Revised! PI-24, a 3-page illustrated fact sheet by Thomas W. Dean and Frederick M. Fishel, details all steps needed to estimate accurately in gallons-per-acre (GPA) how much a properly calibrated boom sprayer will broadcast. Includes references. Published by the UF Department of Agronomy, June 2008.